DETERMINASI NILAI PERUSAHAAN: PERAN PROFITABILITAS, LEVERAGE, DAN FREE CASH FLOW PADA PERUSAHAAN JAKARTA ISLAMIC INDEX PERIODE 2021–2024 - Marvin, Maureen Marcia; Mendari, Anastasia Sri (Catholic University Musi Charitas, 2026)
Purpose : This study aims to test and analyze the influence of profitability leverage and free cash flow on company value at Jakarta Islamic Index within a defined research period Design Methodology Approach : A quantitative approach was applied using secondary data The population consists of companies registered as constituents in the Jakarta Islamic Index The sampling technique employed was purposive sampling resulting in selected companies and corresponding observations Data processing was conducted using multiple linear regression analysis with SPSS Findings : Profitability shows a positive effect on company value in the Jakarta Islamic Index leverage also shows a positive effect on company value In contrast free cash flow does not exhibit a significant effect on company value Practical Implications : Financial strategies and decision making processes in sharia compliant companies can be strengthened through the use of fundamental financial information Originality Value : A more contextual understanding is provided regarding fundamental determinants of company value under dynamic economic conditions while contributing to the literature on company valuation within firms applying specific financial screening criteria